Bibliometric Analysis of Research on “Urology and COVID-19”; Web of Science Example. - Mümtaz DADALI, İbrahim ÜNTAN1; ERŞEKERCİ, Erol; BAĞBANCI, Muhammed Şahin (Ahi Evran Medical Journal, 2024)
Purpose: The study aims to reveal the bibliometric analysis and trends of 1616 studies published in the fields of "Urology and COVID19" since the outbreak of the pandemic. Thus, it is aimed to provide researchers with basic information about the statistical distribution of research on these topics. This study aims to reveal the bibliometric analyzes and trends of 1616 studies published in the “Urology and COVID-19” fields since the pandemic broke out. Thus, it was aimed to provide researchers with basic information about the field of research on these subjects, in which countries it was conducted, and in which journals it was mostly published. Materials and Methods: A bibliometric analysis was conducted on "Urology and COVID-19" for 2020 - 2023 years using the Web of Science Core Collection Database. The results were compared with "Urology" publications of the same period. Trends were also evaluated with different data using free online visualization software (carrot2). Results: A total of 5481 articles cited these studies 13036 times. The most common document type was research article, the most common field was Urology & Nephrology, the most common language was English, the most common journal was the Journal of Urology, the most common publishing country was the United States, and the most common contributing institution was Udice University. Conclusion: This infectious disease, which disrupted the balance of the world, also changed the balance of publications in its favor. Urologists gave more importance to "Urology and COVID-19" research than isolated "Urology" research while fighting against the pandemic.